PKM Introduksi Sediaan Konsentrat Hijauan Rawa Sebagai Sumber Protein Itik Alabio - Danang Biyatmoko; Untung Santoso; Tintin Rostini (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2021)
Abstract Duck feed ingredients are currently still expensive and less affordable for breeders, it is necessary to have alternative quality feed ingredients originating from potential superior swamp plants. The activity aims to provide concentrate preparations from swamp forage as feed ingredients for ducks to reduce feed prices, improve ration quality and income (IOFC) for laying ducks. The activity partner is the Keraton duck group in the Martapura sub-district, Banjar Regency. The activity lasts months. The results of this activity are identification of superior forage originating from swamps that have the potential to be used as feed for laying ducks including Kayapu (Azolla pinnata, aquatic algae (Azolla microphylla, duckweed (Lemna minor), water spinach (Ipomoea aquatica Forsk), water hyacinth (Eichhornia crassipes), water hyacinth (Eichhornia crassipes), taro leaves (Colocasia esculenta L.), genjer (Limnocharis flava), kiambang (Salvinia molesta ) and antanan (Centella asiatica (L.) Urban).There are only four forage concentrates that have a nutrient content of more than 20%, namely kayapu , aquatic algae (azolla microphylla), duckweed (Lemna minor) and water spinach (Ipomoea aquatica Forsk), until they are packaged as swamp forage concentrate products .Feeding trial application of alternative feed ingredients, 30% swamp forage concentrate in duck rations can improve the quality of the main duck ration protein (PK), which resulted in an increase in the number of egg production and the percentage of egg production from 67% to 69.3%, as well as a decrease in ration prices from the price before the activity is IDR 5,630/kg to IDR 4,035/kg after the activity. Feed conversion (FCR) was improved from FCR 6.0 improved to 4.6, egg yolk color increased from 8-9 to 10-11, and IOFC increased from Rp 5.8 million/month to Rp 6.3 million/month. The conclusion shows that the activity of making concentrate preparations is very helpful for farmers increase business profits. Keywords: egg production, forage concentrate, iofc, ration price, swamp forage   Abstrak Bahan pakan itik saat ini masih mahal dan kurang terjangkau peternak, perlu alternatif bahan pakan yang berkualitas asal tanaman potensial unggulan rawa. Kegiatan bertujuan untuk menyediaan sediaan konsentrat asal hijauan rawa sebagai bahan pakan itik untuk menurunkan harga pakan, memperbaiki kualitas ransum dan pendapatan (IOFC) usaha itik petelur. Mitra kegiatan adalah kelompok itik Keraton di kecamatan martapura Kabupaten Banjar. Kegiatan berlangsung dua bulan.  Hasil pelaksanaan kegiatan adalah Identifikasi hijauan unggulan asal rawa yang potensial sebagai pakan itik petelur ada sembilan meliputi kayapu (azolla pinnata, ganggang air (azolla microphylla, duckweed (Lemna minor), kangkung air (Ipomoea aquatica Forsk), eceng gondok (Eichhornia crassipes), daun talas (Colocasia esculenta L.), genjer (Limnocharis flava), kiambang (Salvinia molesta ) dan antanan (Centella asiatica (L.) Urban). Pembuatan konsentrat hijauan hanya ada empat hijauan rawa yang memiliki kadar nutrisi di atas 20% yaitu kayapu, ganggang air (azolla microphylla), duckweed (Lemna minor) dan kangkung air (Ipomoea aquatica Forsk), hingga dikemas sebagai produk konsentrat hijauan rawa.  Feeding trial penerapan bahan pakan alternatif konsentrat hijauan rawa 30% dalam ransum itik mampu memperbaiki kualitas ransum itik utamanya protein (PK), yang berdampak pada peningkatan jumlah produksi telur dan prosentase produksi telur dari 67% menjadi 69,3%, serta penurunan harga ransum dari harga sebelum kegiatan sebesar Rp 5.630/kg menjadi Rp 4.035/kg setelah kegiatan. Konversi pakan (FCR) diperbaiki dari FCR 6,0 membaik menjadi 4,6,  warna kuning telur meningkat dari 8-9 menjadi 10-11, dan IOFC naik dari Rp 5,8 juta/bln menjadi Rp 6,3 juta/bln.  Kesimpulan menunjukkan kegiatan pembuatan sediaan konsentrat sangat membantu peternak meningkatkan keuntungan usaha itik petelur. Kata kunci: harga ransum,  hijauan rawa, iofc, konsentrat hijauan, produksi telur